Chile : Towards Equality of Opportunity, 2006-2010 - World Bank (Washington, DC, 2014)
This package of policy papers aims to provide the Government with new analytical findings, international experiences, as well as a number of options which might be of interest in the deliberations of policy actions that could improve equalities of opportunity in Chilean society. The package includes a Development Policy Review which examines policy options that could help Chile to achieve the twin goals of fast and equitable growth. The Development Policy Review focuses on social protection, education, innovation, private sector development, and the financing of development policies. Further, the package includes five specific Policy Notes which provide additional in-depth discussions on a number of selected topics, all of them important to improving equalities of opportunity in the country. These specific topics had been suggested to us by a number of senior Chilean policy makers over the past months as being of potential interest for the incoming Chilean Government. This presentation of World Bank documents shows, in the second section, some dimensions of inequalities of opportunity in Chile today. The third section summarizes the main messages of the Development Policy Review and the specific Policy Notes in four broad areas of pro-equity policies: strengthening and protecting human capacities; ensuring access to infrastructure services and equitable regional development opportunities; strengthening markets, protecting people against macro-economic shocks and fostering innovation-led growth; and financing pro-equity development policies. Finally, the last section presents the results of some quantifications as to what the results of a number of pro-equity policies could be on growth, poverty, and income inequality.